Instrumentality, empiricism, and rationality in Nuosu divination - Hong, Ze (Religion, brain & behavior, 2025)
We offer an in-depth ethnographic exploration of Nuosu divination, examining its underlying rationale from cognitive perspectives and highlighting its instrumental and empirical components in everyday contexts, such as the clients’ skepticism and diviners’ attempts to signal its integrity and transparency. Challenging suggestions made by some cultural anthropologists, we argue that the Nuosu primarily regard divination as tools and methods that generate information for subsequent decision-making, and place considerable weight on the accuracy of information yielded. We conclude by positing that the question of “why divination” remains and merits further cognitive and cultural evolutionary investigations.